A Surgical Method to Improve the Homeostasis of CSF for the Treatment of Alzheimer’s Disease - Qin, Yang; Gu, Jian W. (Frontiers in Aging Neuroscience, 2016)
Reduced cerebrospinal fluid (CSF) production and increased resistance to CSF outflow are considered to be associated with aging, and are also characteristics of Alzheimer disease (AD). These changes probably result in a decrease in the efficiency of the mechanism by which CSF removes toxic molecules such as amyloid-β (Aβ) and tau from the interstitial fluid space. Soluble Aβ is potently neurotoxic and dysfunction in CSF circulation can accelerate the progression of AD. Current therapies for AD exhibit poor efficiency; therefore, a surgical method to improve the homeostasis of CSF is worthy of investigation. To achieve this, we conceived a novel device, which consists of a ventriculo-peritoneal shunt, an injection port and a portable infusion pump. Artificial CSF is pumped into the ventricles and the artificial CSF composition, infusion modes and pressure threshold of shunting can be adjusted according to the intracranial pressure and CSF contents. We hypothesize that this active treatment for CSF circulation dysfunction will significantly retard the progression of AD.